2015
DOI: 10.1111/his.12685
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and morphological features of collagen type III glomerulopathy: a report of nine cases from a single institution

Abstract: Collagen type III deposits in the subendothelial and mesangial areas. Some patients show global nodular lesions, while others show subtle changes only via PAS/silver staining. Proteinuria and hypertension are the most common symptoms, and the serum creatinine level at biopsy is an independent predictor of the doubling of serum creatinine during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Formalin‐fixed renal tissue was embedded in paraffin using routine procedures. Thin 3 μm sections were stained with hematoxylin and eosin (HE), periodic acid‐Schiff, silver methenamine and Masson's trichrome [15]. Immunofluorescence staining was performed on 3 μm cryostat sections using FITC‐labeled rabbit anti‐human IgG, IgA, IgM, Complement (C) C3, C4 antibodies (Dako Corporation, Carpentaria, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Formalin‐fixed renal tissue was embedded in paraffin using routine procedures. Thin 3 μm sections were stained with hematoxylin and eosin (HE), periodic acid‐Schiff, silver methenamine and Masson's trichrome [15]. Immunofluorescence staining was performed on 3 μm cryostat sections using FITC‐labeled rabbit anti‐human IgG, IgA, IgM, Complement (C) C3, C4 antibodies (Dako Corporation, Carpentaria, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Collagenofibrotic glomerulopathy, also known as primary glomerular fibrosis and collagen type III glomerulopathy, is a rare form of glomerular disease with less than 50 reported cases in the literature. 3,5 CG belongs to the category of non-amyloid non-immunoglobulinderived, organized deposits. 2 Other diseases in this category are fibronectin glomerulopathy and diabetic sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…10 It has been reported in all age groups and in different ethnicities. 3,5 CG is considered a sporadic disease. 9 However, an autosomal recessive type of inheritance affecting some families has been reported predominantly in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous light microscopy studies indicated mesangial expansion with weakly PAS-positive material and negative PAM staining, as well as negative IF results (3,20). Electron microscopy indicates typical curved and scattered collagen fibrils in the subendothelial and mesangial regions with a periodicity of 50-60 nm (21). IHC testing indicates strong expression of type III collagen within the mesangium and along GBMs (13).…”
Section: Discussionmentioning
confidence: 99%